Impact of the Mt. Pinatubo volcaniceruption on the lower ionosphere andatmospheric waves over Central Europe - J. Lastovicka (Annals of Geophysics, 2003)
The very strong volcanic eruption of Mt. Pinatubo in June 1991 directly affected the troposphere and lower and middle stratosphere. Here we look at its effects in the mesopause region as revealed by the radio wave absorption measurements in the lower ionosphere over Central Europe and inferred planetary and gravity wave activity.
The gravity wave activity inferred from the nighttime LF radio wave absorption displays an evident enhancement
for waves of periods of about 2-3 h coinciding with regional measurements of the optical depth of (volcanic) aerosols, while there is no detectable effect for short period waves (T < 1 h). There is no detectable effect in the planetary wave activity inferred from the daytime HF radio wave absorption. As for the absorption itself, the results on the impact of the Mt. Pinatubo eruption do not provide an observable effect.